Spiritual Mental Development Concept and the Implications for Students: Konsep Pembinaan Mental Spiritual dan Implikasinya bagi Peserta Didik - Khadavi, Muhammad Jadid (Universitas Muhammadiyah Sidoarjo, 2023)
Discourse on the concept of spiritual mental development and its implications for students is still very relevant in the current context. Many schools prioritize the achievement of students cognitive values, but pay little attention to the mental-spiritual aspect. As a result, many students have high grades but are unable to adapt to their social environment. This causes cases of juvenile delinquency and an increase in the number of unemployed. This research aims to analyze and discover the concept of spiritual mental development and its implications for students through a qualitative approach. The results of this study indicate that spiritual mental development is an educational institution's effort to produce graduates who have strong survival skills, are knowledgeable, have qualified skills and are based on a spiritual attitude based on Islamic values. Thus, spiritual mental development is very important to be applied in the school environment.